X‑Ray-Induced Modification of the Photophysical Properties of MAPbBr3 Single Crystals - Armaroli, Giovanni; Ferlauto, Laura; Lédée, Ferdinand; Lini, Matilde; Ciavatti, Andrea; Kovtun, Alessandro; Borgatti, Francesco; Calabrese, Gabriele; Milita, Silvia; Fraboni, Beatrice; Cavalcoli, Daniela (ACS applied materials & interfaces, 2021)
Methylammonium lead tribromide (MAPbBr3) perovskite single crystals demonstrate to be excellent direct X-ray and gamma-ray detectors with outstanding sensitivity and low limit of detection. Despite this, thorough studies on the photophysical effects of exposure to high doses of ionizing radiation on this material are still lacking. In this work, we present our findings regarding the effects of controlled X-ray irradiation on the optoelectronic properties of MAPbBr3 single crystals. Irradiation is carried out in air with an imaging X-ray tube, simulating real-life application in a medical facility. By means of surface photovoltage spectroscopy, we find that X-ray exposure quenches free excitons in the material and introduces new bound excitonic species. Despite this drastic effect, the crystals recover after 1 week of storage in dark and low humidity conditions. By means of X-ray photoelectron spectroscopy, we find that the origin of the new bound excitonic species is the formation of bromine vacancies, leading to local changes in the dielectric response of the material. The recovery effect is attributed to vacancy filling by atmospheric oxygen and water.